The trade and FDI effects of EMU enlargement - Jelle Brouwer; Richard Paap; Jean-Marie Viaene (Center for Economic Studies and ifo Institute (CESifo), 2007)
This paper considers the nature and the distribution of trade and FDI effects of a potential enlargement of the European Monetary Union (EMU) to the ten countries that obtained EU membership in 2004. One-way and two-way error component gravity models are estimated using a dataset of unbalanced panel data that combines bilateral trade flows among 29 countries and the distribution of outward FDI stocks among these countries. The results reveal a complementarity between trade and investment and a relationship between trade and exchange rate volatility that depends on the sign of bilateral trade balances. Using a simulation-based technique, we find that estimates of FDI effects of EMU range between 18.5 percent for Poland and 30 percent for Hungary.
Keywords: C33; F21; F31; F33; F36; 330; EMU; exchange rate volatility; foreign investment; trade diversion; vertical integration; Europäische Wirtschafts- und Währungsunion; EU-Erweiterung; Wirtschaftspolitische Wirkungsanalyse; Außenhandelseffekt; Direktinvestition; Wechselkursrisiko; Gravitationsmodell; EU-Staaten; Ungarn; Polen